Disinformasi Jaringan Sosial Tudingan Radikalisme Terhadap Anies Baswedan di Media Sosial Twitter - Radita Gora Tayibnapis; Anastasia Lintang Proborini (Journal on Education, 2024)
The political contestation ahead of the 2024 General Election has begun to be colored by the psychological war of impeachment to hate speech uttered by opposition partisans to bring down political opponents through social media. Various ways and expressions indicating the connection of political actors with reading negative views of society, such as Anies Baswedan's candidacy as a Presidential Candidate for 2024, have begun to be colored by controversy on social media which is associated with radicalism and indications of Anies' connection with banned organizations. In an attempt to dissect this case study, the researcher used a quantitative method based on Big Data to find the distribution of Communication Networks on Twitter social media. Based on the study results, it shows that there is a central role for actors and organizations who dislike Anies Baswedan by using hashtags and mentions to create negative opinions.